Serum concentrations of leptin in pregnant and non‐pregnant bitches. Issue 4 (20th February 2020) - Troisi, Alessandro; Cardinali, Lucia; Menchetti, Laura; Speranza, Roberto; Verstegen, John P.; Polisca, Angela
Abstract: Leptin regulates body weight and several physiological processes including reproduction. We evaluated the circulating levels of leptin in pregnant and non‐pregnant bitches as well as their correlation with body weight, food intake and number of foetuses. Nineteen healthy German shepherd bitches were used and divided in two groups (pregnant n = 12 and non‐pregnant n = 7). Blood samples were collected every 15 days starting from ovulation (Day 0) throughout pregnancy (pregnant group, P) or throughout luteal phase (non‐pregnant group, NP) In pregnant bitches, leptin concentrations increased from the day of ovulation (1.32 ± 0.06 ng/ml) up to day 45 (1.51 ± 0.06 ng/ml; p < .01) and returned to baseline values from day 60 post‐ovulation. In non‐pregnant bitches, leptin concentrations remained constant throughout the whole observation period (estimated marginal mean ± SE=1.33 ± 0.38 ng/ml). Pairwise comparisons showed significant differences between P and NP at day 45 post‐ovulation ( p < .05). Multivariable models indicated that, controlling for time and litter size, there was a positive relationship between leptin concentration and BW ( p < .05) although Pearson coefficients showed that the correlation between BW and leptin was only significant in NP animals at day 45 (r = 0.76, p < .05). The multivariable approach also suggested that, holding BW and time constant, leptin concentrations tend to increase as the number of puppies increased ( p = .06). Our study supports indirectly the contribution of the feto‐placental unit to the circulating maternal leptin concentration.